2014
DOI: 10.1111/pan.12393
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effectiveness of acetaminophen for primary cleft palate repair in young children: a randomized placebo controlled trial

Abstract: Intravenous acetaminophen given to young children undergoing primary cleft palate repair was associated with opioid-sparing effects compared to placebo. The fewer morphine doses during ward stay in both intravenous and oral may be important clinically in some settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…The impact of acetaminophen on pain after cleft palate surgery is further explored in this current issue of Pediatric Anesthesia . Children ( n = 44, 5–12 months) given acetaminophen had less requirement for rescue medication than those given placebo.…”
mentioning
confidence: 99%
“…The impact of acetaminophen on pain after cleft palate surgery is further explored in this current issue of Pediatric Anesthesia . Children ( n = 44, 5–12 months) given acetaminophen had less requirement for rescue medication than those given placebo.…”
mentioning
confidence: 99%
“…A systemic review comparing multiple recent randomized controlled trials showed an opioid-sparing effect as well as decreased adverse effects of opioids when acetaminophen was administered intravenously perioperatively (Wong et al, 2013). Nour et al (2014) conducted a randomized, placebo-controlled trial examining the analgesic effectiveness of postoperative administration of IV and oral acetaminophen for primary cleft palate repair. A decreased opioid requirement after surgery was found with IV acetaminophen but did not show the same efficacy when taken orally.…”
Section: Discussionmentioning
confidence: 99%
“…Is pharmacokinetics making the difference? While the daily dose of paracetamol needed to achieve concentrations above 10 mg/L in non-brain tissues is similar for the rectal and intravenous route in term neonates,5 intravenous6 but not rectal7 paracetamol has been found to reduce opioid requirements in young children after primary cleft palate repair.…”
Section: Commentarymentioning
confidence: 99%